Extending Microsoft excel and Hansen solubility parameters relationship to double Hansen’s sphere calculation - Manuel Díaz de los Ríos; Rubén Murcia Belmonte (SN Applied Sciences, 2022)
Abstract Previous studies have shown the feasibility of using the Microsoft Excel "Solver" add-in to determine the Hansen solubility parameters and the radius of the Hansen sphere. Compounds such as di-block copolymer or ionic liquids are best represented by a Hansen double sphere, calculated with the HSPiP software; the development of other tools for evaluating this type of case is not reported in the literature. This communication provides the steps for the determination of a Hansen double sphere with the help of an evolutionary algorithm of Microsoft Excel, validated with, five study cases reported in the literature, with the HSPiP software itself. Other improvements for Microsoft Excel 365 version are also described. Article Highlights The workbook updated and posted in Hansen Web page is a useful tool available to the research community interesting in Hansen solubility parameters experimental determination and fit either single and double Hansen’ sphere. In some cases, sphere radius is better reduced than with the use of HSPiP. The "Chemicals” sheet has been included with more than 1200 Hansen Solubility Parameters (HSPs) of solvents and compounds. The worksheet named “HSP Solvents Blends and Chi” has been updated with more functionalities, while the worksheet named “Find a Similar Substance” allows the user to search the entire database to find HSPs of compounds that match the constraints declared. Two-dimensional graphics of the HSPs is also available